Determinants of life insurance consumption: Evidence from Zambia - Mulenga, Ben (Graduate School of Business (GSB), 2021)
Life insurance has over the years emerged as one of the drivers of financial sector development. The savings mobilisation and financial intermediation functions have backed the growing importance of this investment source. Low penetration levels in Zambia have pointed to a vast untapped market and a potential source of financial sector development. Life insurance growth prospects in the country remain optimistic on the back of a growing population and increasing urbanisation. This study examined the impact of selected macroeconomic variables, namely income, inflation and financial development on life insurance demand in Zambia using annual time series secondary data from the period 1995 to 2017. The study utilised the Augmented Dickey-Fuller (ADF) test, Vector Autoregressive model (VAR) Autoregressive Distributed Lag (ARDL) and the Error Correction Model (ECM) in conducting econometric investigations. Findings from the study show that financial development negatively influences life insurance, while inflation has a positive effect at a 5% significance level. Further, the study finds no significant long-term relationship between income and life insurance. However, in the shortrun, a unidirectional causal relationship between life penetration and income exist. In conclusion, the study recommends that the Government prioritises the expansion of the financial sector through the central bank and other regulators in the industry. Policy reforms should be aimed at increasing financial inclusion and deepening the financial sector, as well as increasing access to financial services and products. The study further recommends that life insurance companies should augment Government efforts by increasing sensitisation and marketing of life insurance products and services.